Gastric emptying: a contributory factor in gastro-oesophageal reflux activity?. Issue 5 (1st November 2000) - Stacher, G; Lenglinger, J; Bergmann, H; Schneider, C; Hoffmann, M; Wölfl, G; Stacher-Janotta, G
Abstract : AIMS: To evaluate the impact of total and proximal stomach emptying on 24 hour and postprandial reflux as well as the number of reflux episodes per hour in relation to the impact of lower oesophageal sphincter (LOS) pressure, and oesophageal contractile and clearance function. METHODS: Seventy one outpatients (37 female, 34 male; age 23–82 years) with symptoms suggestive of both delayed gastric emptying and reflux referred for further investigations participated in the study. Gastric emptying of a semisolid 1168 kJ meal and oesophageal clearance of a water bolus (supine) were recorded scintigraphically, reflux by 24 hour pH monitoring, and oesophageal motility manometrically. RESULTS: Slow proximal but not slow distal or total stomach emptying correlated with increased 24 hour and postprandial acid exposure and increased number of reflux episodes/hour. No relationship was found between total or proximal emptying and LOS resting pressure, oesophageal contraction amplitude, percentage of failed contractions, or clearance. Multiple linear regression analyses showed that slow proximal emptying and low LOS pressure contributed significantly to both 24 hour (p=0.0007 and p=0.0001) and two hour postprandial acid exposure (p=0.007 and p=0.0001). In contrast, the rate of total emptying contributed to neither 24 hour nor postprandial acid exposure. CONCLUSION: Our data suggest that in contrast with total stomach emptying, the rate of proximal stomach emptying contributes to the extent of 24 hour as well as postprandial acid exposure and the number of reflux episodes/hour.